The Influence of Digital Marketing and Online Customer Reviews on Purchasing Decisions on the TikTok Shop Marketplace (Case Study: Economics Students, Faculty of Economics, Universitas Negeri Makassar) - Mustari; Ratnah S. (International journal of technology and education research, 2026)
The development of digital technology has transformed the landscape of modern commerce, including how consumers make purchasing decisions. The TikTok Shop marketplace, as a social media-based e-commerce platform, leverages this trend to attract and retain consumers through digital marketing strategies and online customer reviews. This study aims to analyze the influence of digital marketing and online customer reviews on purchasing decisions on the TikTok Shop platform, focusing on Economics Education students, Faculty of Economics and Business, Makassar State University (FEB UNM). The research method used was quantitative with a survey approach. Data were collected through questionnaires distributed to 57 randomly selected respondents. The results showed that digital marketing has a significant influence on purchasing decisions. Aspects such as engaging content, promotions through short videos, and direct interaction with consumers through the live streaming feature on TikTok Shop positively contributed to increased interest and purchasing decisions. In addition, online customer reviews were also shown to have a significant influence on purchasing decisions. Positive reviews from previous users and high product ratings increased consumer trust and confidence in making purchases.